Growth through competition, competition through growth : - Odagiri, Hiroyuki (Clarendon Press, 1992)
This book examines two characteristics that lie at the core of Japanese management: growth pursuit not by acquisitions--but by internal investments, as well as the intensive competition within and among Japanese firms. Odagiri also scrutinizes the manner in which these firms maintain flexibility and efficiency under the seemingly rigid system of "lifetime" employment. This work begins with an enquiry into the financial and human aspects of the firm, with particular emphasis on its human portion. The motivation, behavior, and organization of Japanese management as well as the consequences of the system on the Japan's industrial organization and economy are explored. Emphasis is placed on the fact that competition is at the center of the Japanese economy and management style to the same, if not greater, degree as in the West. It is this competition that is enhanced by the growth preference of the Japanese management style and is, in turn, that which makes growth possible.